2012
DOI: 10.1016/j.marpolbul.2012.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Differential biomagnification of PCB, PBDE, Hg and Radiocesium in the food web of the European hake from the NW Mediterranean

Abstract: Consumption of marine organisms represents one of the main exposure sources of contaminants for human populations. To obtain a global view of the contamination in commercial fish in the NW Mediterranean Sea, we analysed four types of priority contaminants (PCBs, PBDEs, Hg and (137)Cs) in the European hake, Merluccius merluccius, from the Gulf of Lions in relation with organism's trophic level (δ(15)N). All contaminants presented a significant increase in concentration in hake muscle with trophic level. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
39
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 65 publications
9
39
1
1
Order By: Relevance
“…Previously, a market basket study in South Korea on raw foods (Na et al, 2013) also reported a similar outcome with some differences in shellfishes. Because PBDEs are prone to bioaccumulation and biomagnification, the trophic levels of each species and their fat content is widely believed to largely affect the PBDE concentrations (Harmelin-Vivien et al, 2012;Hu et al, 2010;Sørmo et al, 2011;Zhang et al, 2010). These trends were also reflected in our study.…”
Section: Meats Meat Products Fishes and Shellfishessupporting
confidence: 67%
“…Previously, a market basket study in South Korea on raw foods (Na et al, 2013) also reported a similar outcome with some differences in shellfishes. Because PBDEs are prone to bioaccumulation and biomagnification, the trophic levels of each species and their fat content is widely believed to largely affect the PBDE concentrations (Harmelin-Vivien et al, 2012;Hu et al, 2010;Sørmo et al, 2011;Zhang et al, 2010). These trends were also reflected in our study.…”
Section: Meats Meat Products Fishes and Shellfishessupporting
confidence: 67%
“…This is a moderately low value compared with those of some other elements (e.g., iron and tin, which can have concentration factors as high as 3 × 10 4 and 5 × 10 5 , respectively) and other contaminants [e.g., mercury and polychlorinated biphenyls (PCBs)] (Harmelin-Vivien et al 2012). Cs also has a limited biomagnification in marine food chains (only a factor of approximately 2) (Kasamatsu 1997, Zhao et al 2001, Heldal et al 2003, Mathews & Fisher 2008, Harmelin-Vivien et al 2012.…”
Section: Figurementioning
confidence: 99%
“…Previous works suggested that radiocesium is the only trace element apart from Hg that may be potentially biomagnified along food chains (Harmelin-Vivien et al, 2012;Heldal et al, 2003;Zhao et al, 2001). In our study, the modeled TTFs were generally higher than the unity for all zooplankton groups, showing evidence of biomagnification potential at this trophic level.…”
Section: Trophic Transfer Factormentioning
confidence: 99%